Reflections on managing government real property. IN Reflections from Scholars and Practitioners [column] an operational free good to a strategic resource - Jones, Trevor Seymour (2019)
These reflections are from the author’s experiences in managing public sector real property from both within the industry and as an adviser to all levels of government, and how this led him to the academic world. These reflections relate to how the mix of practice and academic learning has shaped the author as an individual, as well as how these experiences reflect
upon his work in assisting governments to face the practical challenges presented by changes in public expectations and public governance. The author has learned how academia gives independent authority, credence, validity, and explanation to personal professional experiences and observations, and provides exciting and reasoned intellectual bases for them. Questioning what he has seen has exposed him to areas of organizational culture and behavioral and political science. After all, real property is just concrete, bricks and mortar. Or, is it?
Keywords: Management of government purchasing; Government purchasing of real property; Asset management -- Government policy; Public administration -- Theory and practice; Public finance -- Government policy